2000
DOI: 10.5642/aliso.20001902.05
|View full text |Cite
|
Sign up to set email alerts
|

New Euphorbiaceae from Mexico

Abstract: This article co nta ined descriptions of five new taxa of Me xican Euphorbiaceae. Euphorbia (sub g. Agaloma) na yaren sis is e nde mic to pine-oak woodland in the mount ains of central Nayarit. It appears related to E. so ob yi but differs by possessing linear to linear-ovate leaves. Croton varelae is also endemic to central Nayarit. A key was provided to distinguish this spec ies. a member of sect. Geiseleria, from the sev en othe r Mex ican species of this section. Cr ot on ram illatus var. magniglandulifer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…None of our concatenated analyses indicated that M. mcvaughii , M. obovata , or Manihotoides paucifl ora are closely related, implying that condensed stems and unifl orous infl orescences might have evolved at least twice. Furthermore, these results add support to the hypothesis that these features have evolved in response to arid environments ( Steinmann, 2005 ) given that these three unrelated species are located in some of the driest areas of occurrence of Manihot in Mexico, which also have the highest minimum temperatures. This association might imply that the evolution of stature is infl uenced by water availability, with larger plants being favored in areas where drought is less severe ( Moles et al, 2009 ).…”
Section: Positions Of New North Americansupporting
confidence: 77%
See 3 more Smart Citations
“…None of our concatenated analyses indicated that M. mcvaughii , M. obovata , or Manihotoides paucifl ora are closely related, implying that condensed stems and unifl orous infl orescences might have evolved at least twice. Furthermore, these results add support to the hypothesis that these features have evolved in response to arid environments ( Steinmann, 2005 ) given that these three unrelated species are located in some of the driest areas of occurrence of Manihot in Mexico, which also have the highest minimum temperatures. This association might imply that the evolution of stature is infl uenced by water availability, with larger plants being favored in areas where drought is less severe ( Moles et al, 2009 ).…”
Section: Positions Of New North Americansupporting
confidence: 77%
“…Our results also suggested that the unusual features of Manihotoides ( Rogers and Appan, 1973 ) are examples of the morphological lability in Manihot . Manihotoides paucifl ora shares with Manihot mcvaughii and M. obovata reduced inflorescences ( Martínez-Gordillo et al, 2002 ;Steinmann, 2005 ), and with M. obovata the presence of leaves clustered on short shoots ( Martínez-Gordillo et al, 2002 ;Webster, 1994 ). None of our concatenated analyses indicated that M. mcvaughii , M. obovata , or Manihotoides paucifl ora are closely related, implying that condensed stems and unifl orous infl orescences might have evolved at least twice.…”
Section: Positions Of New North Americanmentioning
confidence: 83%
See 2 more Smart Citations